Towards a Humanitarian Race: A Study in Selected Poems by Billy Collins - AL-HUSSEINI, MIFTEN I.; AL-ZUBBAIDI, HAITHAM K. (Al-Adab Journal, 2022)
The purpose of this article is to analyze selected poetic works of Billy Collins (1941- ), the most popular American poet in the present time, to show a clear line of moral humanitarian preaching that runs under the surface of his often humorous and entertaining poems. The topics discussed in this article include manners, respecting privacy, personal responsibility, self-acceptance, practical living advice, gratitude for life and finding meaning in death. The poems analyzed in this study address a wide range of human issues that are relatable in a global sense. The way Collins delivers these universal messages includes many postmodern devices such as humor, wit, sarcasm, satire and irony. Collins style of writing is freestyle and involves many settings and themes of the everyday and matters that the common person would encounter. The accessibility of his writing has gained him widespread public appeal and his lessons for humanity set him apart from the poetry that is only for entertainment value.